Weeds of Kentucky and Adjacent States : A Field Guide - Haragan, Patricia Dalton, 1953- (Book collections on Project MUSE., 1991)
Because of its central location and geographical diversity, Kentucky is home today to perhaps the richest diversity of non-native plants east of the Rocky Mountains, and weeds make up a large component of the state's flora and vegetation. Many of Kentucky's weeds are immigrants that came to the New World from the Old and were brought to Kentucky by travelers, explorers, and settlers. This guide to the identification of 160 weeds commonly found in crops, pastures, turf, and along roadsides provides ecological, geographical, and ethnobotanical information with each species description. It is the.